Asymptotic integration of systems of two wave equations with small parameter - Krylovas, Aleksandras (Lietuvos matematikos rinkinys, 2016)
In this article we consider a hyperbolic system of two weakly nonlinear equations. Coefficients of the equations and initial conditions are periodical functions of the space variable. A multi-scale perturbation technique and integrating along characteristics are used to construct asymptotic series without secular members. The scheme of asymptotic integration is applied to analysis of oscillations of nonlinear non-homogeneous strings.